Study on the Evolution of Public Space in Historic Cities from the Perspective of Changing Needs of Users: A Case of Harbin City, China - Wu, Zhongyang; Zhao, Zhiqing (International Planning History Society Proceedings, 2024)
As a witness and carrier of urban history, the evolution of public spaces is of significant importance for the study of urban historical and cultural preservation. Harbin, a representative historical city in Northeast China, emerged gradually in 1898 due to the construction of the Middle East Railway. During this period, Chinese and foreign nationals coexisted and jointly built the city, marking a unique historical period.This paper presents an in-depth study of the evolution of public spaces in Harbin's historical urban areas from 1898 to 1945, with a focus on changes in user needs. The paper analyses the urban construction background of Harbin, explores the changes and characteristics of user needs in public spaces, and details the evolution of Harbin's public spaces from 1898 to 1945. This encompasses the initial foundation period, functional evolution period, and cultural reshaping period. This demonstrates the construction of the public space framework, the diverse development of functions, and the integration of multifunctionality. This study not only reveals the patterns of evolution in Harbin's public spaces, but also provides valuable references for the study of public spaces in other historical cities.